Structural acoustic coupling resonance of hindu temples - Wijesiriwardana, R.; Vignarajah, M.; Kathirgamanathan, P.; Walgama, K. (University of Jaffna, 2017)
Some ancient constructions over the world exhibit acoustic resonance chambers [1, 7]. Acoustic resonance of Pyramids [1], Stupas [2,6,7], Cathedrals [3,4,12] and Mosques [5] have been studied and they closely resembles the Alpha, Theta and Gamma waves of EEG spectrum [11]. Moreover, these EEG frequencies corresponds to the alert calmness that conducive for mental composure and general well being [6, 7]. Research has also showed that these frequencies are also closerto the Shumann resonance frequencies [9,10]. Even though, acoustic resonances are in the mechanical vibration domain theresearchers have found these vibration energies may have transformed into equivalent electromagnetic frequencies (EEG and Shumann bandwidth) [1,6]. This conversion is mostly may have achieved in ancient resonance chambers by properly using special quartz crystals [2,6,7] and getting them to vibrate by acoustic energies. In addition, some of these acoustic resonance chambers also have vibrating frequencies which are octaves of 528 Hz and 432 Hz [13]. These frequencies are also known to be healing frequencies commonly used in sound therapies [14]. Limited research has been done to understand the acoustic resonance chambers of Hindu Temples. Two types of acoustic resonance chambers can be found in Hind Temples. The first one is the “Moolastana” chamber and the other is the inner core (path). We have studied, and measured acoustic resonance frequencies of inner core chamber in a Hindu Temple in Sri Lanka.
Keywords: Structural acoustic resonance; Hindu Temples; Finite element modelling; Reverberation time